Konstruksi Masyarakat Pasar Blumbungan Tentang Penerapan Protokol Kesahatan di Masa Pandemi Covid-19 - Mahendra, Aditya Alif (Paradigma, 2022)
The market is a place where people carry out buying and selling activities. So that during the pandemic, the market became a vulnerable place in the spread of Covid-19. The government’s health protocol policy aims to reduce the spread of Covid-19 cases. However, at the Blumbungan Pamekasan Market, the majority of people do not implement the health protocol as the government wants. This study uses a qualitative method using Peter L Berger’s social construction theory as its analytical knife. The results of this study show that the Blumbungan market community complies with health protocols only as a form of formality to avoid sanctions and reprimands given by the covid task force. most people believe that covid is an old disease that has existed for a long time so there is no need to worry too much, the people of Blumbungan market have high confidence so they don’t feel afraid of covid. The Blumbungan market community tends to be afraid of losing material factors rather than health factors such as the PMK outbreak in cattle, the Blumbungan market community fears more than Covid because it can affect the selling price of the cattle there. Keywords: covid-19, social construction, health protocol, community